Content Analysis of English 101&102 Courses, Scientific Section at the Faculty of Education, Sana’a University - Almuslimi, Fazee Khalid Alezi (Journal of Curriculum and Teaching Methodology, 2022)
The present study aimed to evaluate English 101 and 102 textbooks of the Scientific Section at Faculty of Education, Sana’a University in order to 1) see the extent to which they correspond to the objectives prescribed in the courses descriptions by the curriculum designers in the Faculty of Education, Sana’a University and 2) check the suitability of the textbooks based on the standards of a comprehensive well- designed EFL textbook from the points highlighted in the data instrument. This study was a quantitative descriptive study. To achieve these objectives, a ready- made checklist instrument was adopted for measurement. The sample was 101 and 102 textbooks. To attain the data objectively, the checklist was handed to 10 raters including the researcher. Then, data was analyzed statistically using SPSS has been used to analyze the data. The findings of the checklist data analysis revealed that the textbooks are in correspondence with the objectives of the faculty. It is also found that the overall judgment for the textbooks is estimated as Good. The study recommended that certain modifications has to be taken into account to remedy such shortcomings.
Keywords: Content Analysis; Textbook